1991
DOI: 10.1002/bsl.2370090209
|View full text |Cite
|
Sign up to set email alerts
|

Expert witnesses in child abuse cases

Abstract: This article discusses the need for expert testimony and the criteria for admissibility of such testimony in child abuse cases. It addresses the scope of expert testimony in both physical and sexual abuse cases with respect to (a) descriptive and diagnostic issues, (b) witness credibility issues, and (c) legal issues. In particular, the article focuses on the admissibility of expert testimony on the battered child syndrome, the child sexual abuse accommodation syndrome, and observations of behavior with anato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Experts in child sexual abuse cases mainly provide two types of expert testimony (Sagatun, 1991). In the trial of an alleged perpetrator, experts may be utilized by the prosecution to rehabilitate child testimony following an attack by the defense.…”
Section: Expert Testimonymentioning
confidence: 99%
See 1 more Smart Citation
“…Experts in child sexual abuse cases mainly provide two types of expert testimony (Sagatun, 1991). In the trial of an alleged perpetrator, experts may be utilized by the prosecution to rehabilitate child testimony following an attack by the defense.…”
Section: Expert Testimonymentioning
confidence: 99%
“…Historically, the model of sexual abuse reactions that is most popular in the courtroom (Sagatun, 1991) is the Child Sexual Abuse Accommodation Syndrome (CSAAS, Summit, 1983). Summit proposed this model based on his clinical experience with child victims of sexual abuse.…”
Section: Trauma Models and Post Hoc Reasoningmentioning
confidence: 99%
“…Psychological and legal scholars have begun to examine the legal and scientific status of expert testimony in child sexual abuse cases (e.g., Doris, 1991; McCord, 1986; Roe, 1985; Serrato, 1988). In particular, scholars have discussed the admissibility and possible effects of different types of testimony (e.g., syndromal, witness credibility, or behavioral evidence) that could be offered by an expert psychological witness in the context of a child sexual abuse trial (e.g., Levy, 1989; Sagatun, 1991). These different types of testimony vary in their scientific status within the field of psychology, and to the extent that beliefs shape our perceptions of evidence, differential juror perceptions of scientific status may result in differential effects of expert testimony on legal decision making.…”
Section: Influence Of Expert Testimony On Juror Judgmentsmentioning
confidence: 99%
“…Critics have also debated the merits of another type of expert testimony based on children's behavioral responses: expert testimony reporting on clinical interviews with children during which anatomically detailed (AD) dolls are used as an investigative or therapeutic tool (Koocher et al, 1995;Sagatun, 1991). Some therapists and investigators have used AD dolls to aid children when they describe their experiences of abuse (Everson & Boat, 1994).…”
Section: Amomicauy Detailed Dolls Evidencementioning
confidence: 99%
“…Aithough some empirical research comparing the play of abused and nonreferred children has supported the assumption that abused children are more likely to engage in sexualized behavior with AD dolls than are nonabused children (e.g., August & Forman, 1989; Jampole & Weber, 1987; White, Strom, Santilli, & Halpin, 1986), other studies have not found differences between these groups (e.g., Cohn, 1991;Kenyon-Jump, Bumette, & Robertson, 1991). Unfortunately, some of this research suffers from methodological constraints, such as the lack of information regarding the reliability of behavioral coding, small sample sizes, and lack of experimenter unawareness of group (e.g., abused vs. nonabused) membership (for methodological criticisms, see Koocher et al, 1995;Levy, 1989;Maan, 1991;Sagatun, 1991).…”
Section: Amomicauy Detailed Dolls Evidencementioning
confidence: 99%